Forward genetics identifies Kdf1/1810019J16Rik as an essential regulator of the proliferation-differentiation decision in epidermal progenitor cells - Lee, Sunjin (2013)
Cell fate decisions during embryogenesis and adult life govern tissue formation, homeostasis and repair. Two key decisions that must be tightly coordinated are proliferation and differentiation. Overproliferation can lead to hyperplasia or tumor formation while premature differentiation can result in a depletion of proliferating cells and organ failure. Maintaining this balance is especially important in tissues that undergo rapid turnover like skin however, despite recent advances, the genetic mechanisms that balance cell differentiation and proliferation are still unclear. In an unbiased genetic screen to identify genes affecting early development, we identified an essential regulator of the proliferation-differentiation balance in epidermal progenitor cells, the Keratinocyte differentiation factor 1 (Kdf1; 1810019J16Rik) gene. Kdf1 is expressed in epidermal cells from early stages of epidermis formation through adulthood. Specifically, Kdf1 is expressed both in epidermal progenitor cells where it acts to curb the rate of proliferation as well as in their progeny where it is required to block proliferation and promote differentiation. Consequently, Kdf1 mutants display both uncontrolled cell proliferation in the epidermis and failure to develop terminal fates. Our findings reveal a dual role for the novel gene Kdf1 both as a repressive signal for progenitor cell proliferation through its inhibition of p63 and a strong inductive signal for terminal differentiation through its interaction with the cell cycle regulator Stratifin.